PROBLEMS FACED IN TEACHING ENGLISH IN SECONDARY SCHOOLS AND EFFECTIVE SOLUTIONS - Bayjanov Saparniyaz; Urazmatova Manzura (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This paper explores the multifaceted challenges faced by English language teachers in secondary education and offers practical strategies to overcome them. It starts by emphasizing the growing importance of English as a global lingua franca and highlights the early integration of foreign language instruction in developed countries. The paper then outlines three major categories of problems: inadequate teaching materials, ineffective curriculum design, and limited technological resources. Each issue is discussed in depth, supported by real-life examples and comparative insights, such as referencing the educational framework of the Netherlands. The second part presents innovative teaching methods and student-centered strategies, including techniques for tense instruction and vocabulary acquisition. These are designed to enhance both comprehension and retention. The work concludes by reiterating the vital role of educators and parents in fostering language learning and promoting educational advancement. Overall, the referat balances theoretical observations with actionable classroom solutions.